Apparent digestibility in marine mutton snapper juveniles and digestive activity of enzymes (Research, Society and Development, 2020)
The marine species of snapper, Lutjanus analis, has carnivorous eating habits and with potential for cultivation. The aim of this study was to evaluate the apparent digestibility coefficient (CDA) of mutton snapper, and to evaluate its enzymatic profile after feeding with vegetable and animal protein sources. CDA was the indirect method of fecal collection, using chromic oxide as a biological marker. Eight hundred fish, with an average weight of 28.0 ± 2.58 g, were acclimated for 15 days in a net tank (2 m³), ​​and installed in the same collection environment. The acclimatization of 54 fish was carried out in digestibility aquariums (200 L), and the collection of feces started. For mutton snapper, the supply of octopus flour improves (P